Analisis Komparasi Pelayanan Tol Laut Dalam Penurunan Disparitas Harga Komoditas Pada Rute Pelayanan Kawasan Barat Dan Kawasan Timur Indonesia - Raga, Paulus; Firdaus, Rafly; Nugroho, Prastyo Bayu (Institut Transportasi dan Logistik Trisakti, 2025)
Sea Highway is a program for the Implementation of Public Service Obligations for Port-to-Port Sea Transport of Goods from and to 3TP (Disadvantaged, Remote, Outermost, and Border) areas that are not yet served by commercial sea transport, the performance of the Sea Toll Road recorded positive growth which was marked by the continued increase in the number of annual cargoes and the number of ports of call as well as the number of route services which were quite large and the high demand for sea toll vessel services to the regions was not commensurate with the large number of goods offered as return cargo. Sea toll vessels are still a major problem. Because there are still many superior products produced in the 3TP area that do not meet requirements, backloading is always a major problem in the Sea Highway program. Commodity price disparity is a complex and significant economic phenomenon that affects national market stability. This study aims to analyze commodity price disparity trends from 2021 to 2023 with a focus on factors that influence price fluctuations, the global the national, commodity fuel price fluctuations, logistics costs, the number and type of ships available, bad weather, demand and supply imbalances. The analytical methods used include collecting secondary data from various literature sources and commodity price reports basic goods and important goods as well as a descriptive approach to describe commodity price patterns and dynamics. Bapokting stability which is an effort to reduce commodity price disparities, this study investigates the important role of basic goods and important goods stabilization in the context of reducing commodity price differences between regions. Policy and regulatory methods issued by regulatory bodies can affect commodity price stability, for example in managing commodity markets to support a sustainable reduction in commodity price disparities